2006
DOI: 10.2172/898511
|View full text |Cite
|
Sign up to set email alerts
|

The Refuelable Zinc-air Battery: Alternative Techniques for Zinc and Electrolyte Regeneration

Abstract: An investigation was conducted into alternative techniques for zinc and electrolyte regeneration and reuse in the refuelable zinc/air battery that was developed by LLNL and previously tested on a moving electric bus using cut wire. Mossy zinc was electrodeposited onto a bipolar array of inclined Ni plates with an energy consumption of 1.8 kWh/kg. Using a H 2depolarized anode, zinc was deposited at 0.6 V (0.8 kA/m 2 ); the open circuit voltage was 0.45 V. Three types of fuel pellets were tested and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Cooper et al also demonstrated that the size of Zn particles should be limited to below~0.85 mm to insure continuous feed [93]. The refilling time for a typical application is about 10e20 min, which is relatively long compared with gasoline refilling.…”
Section: Mechanically Rechargeable Zn-air Fuel Cellsmentioning
confidence: 99%
“…Cooper et al also demonstrated that the size of Zn particles should be limited to below~0.85 mm to insure continuous feed [93]. The refilling time for a typical application is about 10e20 min, which is relatively long compared with gasoline refilling.…”
Section: Mechanically Rechargeable Zn-air Fuel Cellsmentioning
confidence: 99%
“…Zn particles produced by different methods have been tested, including cut wire chunks, compacted electrodeposited dendrites, Zn spheroids reconstructed electrochemically in a spouted bed reactor (see, e.g., Fig. 11); zinc pellets are preferred to compacted dendrites owing to their better fluid dynamic behavior [93,[99][100][101][102]. The spent Zn particles, along with the KOH electrolyte, are replaced hydraulically by pumping from an external tank.…”
Section: Mathematical Modeling Of Electrically Rechargeable Zn-air Bamentioning
confidence: 99%
“…The main obstacles can be briefly summarized as follows: (i) poor recharge-ability, (ii) low utilization of the anode, (ii) sluggish kinetics of the cathode, (iii) longevity challenge. Compared with the Zn-air battery, the Zn-air fuel cell (ZAFC) offers several benefits, such as higher specific energy density, more attractive costs, better environmental compatibility and faster onsite refueling which requires only a standard electrical supply [1][2][3][4]16,19,20]. It also has the potential of achieving the performance of the state-of-art H2-air fuel cells used as energy converters [1].…”
Section: Figurementioning
confidence: 99%
“…It was well realized in the 1960s that such batteries could have a high potential and wide applications if a low-cost zinc anode was available. Then the use of hydrophobic Teflon film made the high-energy Zn-air button cell come to being, which has since become a dominant power source for hearing aids [5,19,20]. Recently, technologies based on mechanical recharging have demonstrated significant progress [16,19,20], which led to practical availability of Zn-air systems with power from 170 to 350 Wh/kg.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation